Ectopic cervical thymus in children: Clinical and radiographic features. (28th August 2019) - Purcell, Patricia L.; Marquez Garcia, Juan; Zawawi, Faisal; Propst, Evan J.; Papsin, Blake C.; Blaser, Susan I.; Wolter, Nikolaus E.
Abstract : Objectives: Ectopic thymus is rare and can be a diagnostic challenge. This study evaluated the management of children radiographically diagnosed with ectopic cervical thymus. Methods: A retrospective review of 100 patients was performed. Data related to clinical presentation, radiological imaging, pathology, and management were collected. Changes in lesion volume were tracked over time. Clinical characteristics were compared based on lesion location in the neck using analysis of variance modelling. Results: There were 115 lesions with radiographic features of ectopic cervical thymus (15 children had bilateral lesions). Diagnosis was based on ultrasound in 98% of patients, magnetic resonance imaging in 18%, and computed tomography in 11%. Mean (SD) follow‐up duration was 2 (2.2) years. Forty‐four percent (51/115) of lesions involved the thyroid gland, 29% (33/115) were in the central neck but separate from the thyroid, 18% (21/115) had mediastinal extension, and 8% (9/115) involved the submandibular region. Location was unclear for two patients. Submandibular lesions were on average 12.4 cm 3 larger (95% CI, 8.2, 16.6) than mediastinal lesions at diagnosis, P  ≤ .001. Volume of thymic tissue decreased over time, from a mean (standard deviation [SD]) volume of 4.3 cm 3 (9.2) at initial ultrasound to 2.7 cm 3 (6.1) at final ultrasound (paired t‐test, P = .008). Only two patients required surgery: one for compressive symptoms, and the other to rule out malignancy. Conclusion: Ninety‐eight percent of children with ectopic cervical thymus were managed conservatively without issues. We propose a classification system based on location to ease communication among clinicians and to help follow these lesions over time. Level of Evidence: 4, case series Laryngoscope, 130:1577–1582, 2020